2008
DOI: 10.1161/strokeaha.107.503193
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Lp-PLA 2 and Lysophosphatidylcholine in Symptomatic Carotid Atherosclerotic Plaques

Abstract: Background and Purpose-Circulating lipoprotein-associated phospholipase A 2 (Lp-PLA 2 ) has emerged as a novel biomarker for cardiovascular diseases. However, the correlation between the plaque expression of Lp-PLA 2 and plaque oxidative stress, inflammation, and stability as well as the clinical presentation remains poorly defined, especially for cerebrovascular disease. Therefore, this study was performed to test the hypothesis that Lp-PLA 2 expression is higher in symptomatic than in asymptomatic carotid pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
113
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 41 publications
16
113
0
2
Order By: Relevance
“…A recent analysis of plaque specimens obtained after carotid endarterectomy demonstrated increased Lp-PLA 2 expression in patients with recent TIA or stroke compared to asymptomatic patients, and a correlation between Lp-PLA 2 content and markers of oxidative stress, inflammation and instability. 3 The results of our study provide further support for the role of Lp-PLA 2 as a biomarker of unstable atherosclerotic plaque. Both Lp-PLA 2 mass and activity were significantly associated with symptomatic Ͼ50% large vessel stenosis, but not with cardioembolism, consistent with a specific role in atherosclerotic disease.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A recent analysis of plaque specimens obtained after carotid endarterectomy demonstrated increased Lp-PLA 2 expression in patients with recent TIA or stroke compared to asymptomatic patients, and a correlation between Lp-PLA 2 content and markers of oxidative stress, inflammation and instability. 3 The results of our study provide further support for the role of Lp-PLA 2 as a biomarker of unstable atherosclerotic plaque. Both Lp-PLA 2 mass and activity were significantly associated with symptomatic Ͼ50% large vessel stenosis, but not with cardioembolism, consistent with a specific role in atherosclerotic disease.…”
Section: Discussionsupporting
confidence: 69%
“…Lipoproteinassociated phospholipase A 2 (Lp-PLA 2 ) and C-reactive protein are 2 candidate markers which have been associated with inflammation and plaque instability in histopathologic studies of the carotid arteries. 3,4 The primary aims of this study were to determine whether measurement of LpPLA 2 and highsensitivity C-reactive protein (CRP) could improve riskstratification of patients with TIA and to examine the relationship between these blood markers and TIA mechanism.…”
mentioning
confidence: 99%
“…For each isolation, 90 μL DNase incubation buffer was pipetted into a sterile 1.5 μL reaction tube, 10 μ of DNase I working solution was then added, factors, many inflammatory biomarkers in blood or damaged atherosclerotic plaque are useful for assessing the potential risk of cardiovascular diseases, monitoring disease propagation, and predicting the outcome in various clinical settings [1][2][3][4][5][6][7][8][9][10] . Of these biomarkers [1][2][3][4][5][6][7][8][9][10] , lipoprotein-associated phospholipase A2 (Lp-PLA2) has recently been described as a novel biomarker which is strongly associated with atherosclerosis-related inflammatory processes and plaque instability in histopathologic studies of the coronary and carotid arteries [10][11][12] . Lp-PLA2, also known as platelet-activating factor acetylhydrolase, is produced predominantly by monocyte-derived macrophages, T-lymphocytes and mast cells [13][14][15] .…”
Section: Protocol For Rna Extractionmentioning
confidence: 99%
“…(Table 3) The logistic regression test revealed that older age ( ≥ 65 years old), diabetes mellitus (DM), a positive past history of significant coronary artery obstruction treated by percutaneous coronary intervention (PCI) and the presence of significant ECCA stenosis were strongly associated with elevated Lp-PLA2 mRNA expression of PBMNCs. factor which may promote the generation of oxidized LDL-C and free fatty acid with subsequent direct participation in the formation and rupture of carotid plaques 10,12,15,18,19) . Our results also revealed a strong association between significant coronary artery or ECCA stenosis and elevated Lp-PLA2 mRNA expression of PBMNCs.…”
Section: Comparison Of Baseline Characteristics Between Patients Withmentioning
confidence: 99%
“…The macrophage foam cells generate reactive oxygen species (ROS), produce TNF-α and IL-1, and MMP-9 that promote atherosclerosis, degrade the fibrous cap, and eventually lead to plaque rupture [14]. Recent studies also showed that carotid atherosclerotic plaques from patients symptomatic of stroke had higher expression of lipoprotein-phospholipase A 2 (Lp-PLA 2 )/PAF acetylhydrolase, lyso-PC, OxLDL, macrophage content and MMP-2 compared to carotid plaques from asymptomatic patients [15].…”
Section: Atherosclerosis Is a Risk Factor For Strokementioning
confidence: 99%